Climate Litigation and Hydrological and Meteorological Disasters in the Taquari Valley, Rio Grande do Sul - Almeida, Giovani Spinelli de; Silva , Anderson Moraes da (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT:Objective: This study aims to demonstrate how climate litigation contributes to climate adaptation and resilience in the Taquari Valley, located in the state of Rio Grande do Sul, Brazil. It examines the role of climate litigation as a tool for holding public entities (municipalities, the state of Rio Grande do Sul, and the federal government) accountable.Methodology: The analysis draws upon the records of the Public Civil Action (No. 5001898-69.2024.4.04.7114) filed by the Federal Public Prosecutor’s Office, which addresses climate-related disasters that occurred in the Taquari Valley in 2023 and 2024. The study focuses on the municipalities of Arroio do Meio, Bom Retiro do Sul, Colinas, Cruzeiro do Sul, Encantado, Estrela, Lajeado, Muçum, and Roca Sales. It also references data available in the Integrated Disaster Information System (S2iD) of the Ministry of Regional Development (MDR) concerning the recognition of climate disasters in the aforementioned municipalities.Originality/Relevance: The study highlights the recognition by the MDR of flash floods, floods, and heavy rainfall events in the municipalities of Arroio do Meio, Bom Retiro do Sul, Colinas, Cruzeiro do Sul, Encantado, Estrela, Lajeado, Muçum, and Roca Sales. It analyzes the Public Civil Action (No. 5001898-69.2024.4.04.7114) filed by the Federal Public Prosecutor’s Office and discusses the role of climate litigation in the context of climate disasters.Results: In 2023, the MDR recognized 11 heavy rainfall events and one flash flood in the municipalities under analysis. In 2024, 13 heavy rainfall events and two floods were recorded. These events caused significant social, environmental, and economic impacts in the Taquari Valley. Climate litigation demands that municipalities develop more robust, integrated, and sustainability-oriented action plans, while also ensuring that government entities fulfill their duty to protect the environment by promoting urban planning aligned with natural resource conservation and climate change mitigation.Theoretical/Methodological Contributions: The research adopts a multidisciplinary approach to analyze hydrological and meteorological disasters in the Taquari Valley and the role of climate litigation in mitigating the impacts of such extreme climate events through a case study.Social and Environmental Contributions: Climate litigation emerges as a crucial instrument to hold public entities accountable and to promote the changes necessary for climate adaptation and resilience in affected municipalities. It underscores the urgency of integrated and participatory public policies that ensure environmental protection and climate justice in Brazil.
Keywords: Climate disasters; Public civil action; Public policy